PEMROGRAMAN TRAINING UNIT VACUUM-HELD HANDLING DEVICE DENGAN PROGRAMMABLE LOGIC CONTROLLER (PLC) - , AZIS MUSTOFA, Andhi Akhmad Ismail, S.T., M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Automation is a technologi which apply mechanical, electrical, and computerizing system to operate, execute and handle system, commonly in manufacturing process. The aim of automation is to decrease loss time and to control sequences process. There are three points of automation, input, process, and output. Programmable Logic Controller or PLC is one of the equipment in automation as a processor in the automation process which is used to eliminate relays as a logic contoller in a control process system of automation. This study make a program for training unit vacuum-held handling device. The strong point of this study especialy in making PLC program which known as ladder diagram. There are some methods used in this study. The fisrt is collecting information from literature and learning from person who competent in this case. The second is learning this training unit such as sensor, solenoid, cylinder and other component. The last is analyzing the process which will be executed to make PLC program. The result of this report has points conclusion, all processes are running very well and the PLC program can be applied at the training unit.